2015
DOI: 10.1128/aem.00931-15
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Quantitative PCR and Droplet Digital PCR Multiplex Assays for Two Genera of Bloom-Forming Cyanobacteria, Cylindrospermopsis and Microcystis

Abstract: The increasing occurrence of harmful cyanobacterial blooms, often linked to deteriorated water quality and adverse public health effects, has become a worldwide concern in recent decades. The use of molecular techniques such as real-time quantitative PCR (qPCR) has become increasingly popular in the detection and monitoring of harmful cyanobacterial species. Multiplex qPCR assays that quantify several toxigenic cyanobacterial species have been established previously; however, there is no molecular assay that d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 41 publications
4
42
0
Order By: Relevance
“…For routine diagnosis of microorganisms and viruses, qPCR has been shown to be the most cost-effective and time-effective platform, which is in agreement with other studies [ 38 , 39 ]. The minor differences in estimations of cost-effectiveness and time-effectiveness for qPCR and the QX100 system between the reports mentioned and our calculations are probably due to different prices for consumables, labour fees and indirect costs between countries, and different optimization of analysis protocols in terms of time.…”
Section: Discussionsupporting
confidence: 90%
“…For routine diagnosis of microorganisms and viruses, qPCR has been shown to be the most cost-effective and time-effective platform, which is in agreement with other studies [ 38 , 39 ]. The minor differences in estimations of cost-effectiveness and time-effectiveness for qPCR and the QX100 system between the reports mentioned and our calculations are probably due to different prices for consumables, labour fees and indirect costs between countries, and different optimization of analysis protocols in terms of time.…”
Section: Discussionsupporting
confidence: 90%
“…The failure of the duplex system may be caused by differences in primer concentration, probe concentration, polymerase/dNTP/buffer concentration, annealing/extension time and amount of template DNA [71,72,73,74]. Similarly, previous studies have also shown that the amount of template DNA affects its detection in multiplexed systems [51,58,59,60], where the detection of low concentration genes was inhibited by the high concentration ones. In this study, the Ct values for the rpo C1 gene in these three uniplex-based samples were 9–10 cycles smaller than those for the pks gene, suggesting that abundance of the pks gene in the sample was much lower (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The disadvantages of multiplex qPCR are related to its laborious optimization steps. These steps are required because of the competition between primers or between targets, cross-oligo interactions and difficulties in quantifying the gene targets in complex samples containing predominantly background DNA [ 96 , 97 ]. The determination of absolute 16S rRNA gene copy numbers can also be problematic with qPCR because of the variability in the number of these genetic loci in the genomes of different cyanobacteria species.…”
Section: Qpcr For Cyanotoxinsmentioning
confidence: 99%